Average Error: 0.0 → 0.0
Time: 8.5s
Precision: 64
$1 - \left(x \cdot x + y \cdot y\right)$
$1 - \left(x \cdot x + y \cdot y\right)$
1 - \left(x \cdot x + y \cdot y\right)
1 - \left(x \cdot x + y \cdot y\right)
double f(double x, double y) {
double r13506 = 1.0;
double r13507 = x;
double r13508 = r13507 * r13507;
double r13509 = y;
double r13510 = r13509 * r13509;
double r13511 = r13508 + r13510;
double r13512 = r13506 - r13511;
return r13512;
}


double f(double x, double y) {
double r13513 = 1.0;
double r13514 = x;
double r13515 = r13514 * r13514;
double r13516 = y;
double r13517 = r13516 * r13516;
double r13518 = r13515 + r13517;
double r13519 = r13513 - r13518;
return r13519;
}



# Try it out

Results

 In Out
Enter valid numbers for all inputs

# Derivation

1. Initial program 0.0

$1 - \left(x \cdot x + y \cdot y\right)$
2. Final simplification0.0

$\leadsto 1 - \left(x \cdot x + y \cdot y\right)$

# Reproduce

herbie shell --seed 1
(FPCore (x y)
:name "1 - (x*x + y*y)"
:precision binary64
(- 1 (+ (* x x) (* y y))))